The Effectiveness of Using Problem-Based Learning (PBL) in Mathematics Problem-Solving Ability for Junior High School Students - Febrinna Marchy; Atma Murni; Kartini kartini; Ilham Muhammad (AlphaMath : Journal of Mathematics Education, 2022)
This study aims to determine the effectiveness of the Problem Based Learning model in improving students' problem solving abilities. This is a quasi-experimental study using the Nonequivalent Pretest-Posttest Control Group Design. Students in seventh grade at SMP Negeri 32 Pekanbaru comprised the whole study population. In this research, the sample comprised two classes: VII3 as the experimental class and VII1 as the control class. This study utilizes the beginning mathematical ability test (KAM) and the mathematical problem-solving ability test as its instruments. The class of the sample was determined using the KAM test findings. The data were evaluated using the similarity test of two independent sample t-tests, which was preceded by tests for normality and homogeneity of variance. Students who participated in Problem-Based Learning had greater growth in their ability to solve mathematical problems than students who participated in conventional learning.